Positive solutions for parametric nonlinear nonhomogeneous Robin problems - Aizicovici, S. (2018)
We consider a parametric nonlinear Robin problem driven by a nonhomogeneous differential operator. Using variational tools together with suitable truncation and perturbation techniques, we prove a bifurcation-type theorem describing the dependence of the set of positive solutions on the parameter.